Students’ Perception of their Math Anxiety when Shifted to Online Learning - Chuang, Maricris; Therrese C. Santos; Sean Kalel C. Garcia (SEAMEO SEAMOLEC, 2024)
Abstract Schools suddenly shifted from face-to-face to online classes because of the COVID-19 pandemic. The abrupt change may increase students’ math anxiety. The paper aims to study junior high school students’ perception of math anxiety when they shifted to online learning; 120 high school students were surveyed. The survey tool is a 4-point Likert scale consisting of 15-item statements. Descriptive statistics, ANOVA, and T-test were used for data analysis. Results show that students agreed that their math anxiety levels increased during online learning. There is a statistically significant difference in math anxiety levels between genders and among grade levels. Most students prefer face-to-face classes because they feel their math anxiety level increased during online classes. Teachers should implement different learning strategies to help students learn more effectively and decrease anxiety.Keywords: Face-to-face learning, Math anxiety, Online learning